Defining and Assessing the Governance of Agrarian Sustainability - BACHEV, Hrabrin (Journal of Advanced Research in Law and Economics, 2016)
The goal of this paper is to suggest a modern and practical framework for analyzing and assessing the system of governance of agrarian sustainability. New interdisciplinary New Institutional Economics framework (combining economics, organization, law, sociology, behavioral and political sciences) is incorporated and agrarian sustainability property defined, principle mechanisms and modes of governance (institutions, market, private, public, hybrid) of agrarian sustainability classified, and a holistic approach for identifying components and factors, assessing efficiency, and improving the system of governance presented. Suggested framework is to be further discussed and improved while its application requires new type of micro and macro-economic data for agents’ preferences and behavior, activities and efficiency of agrarian organizations, effects and impacts on social, community and natural environment, etc.